2005
DOI: 10.1159/000082383
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic mapping in maize

Abstract: Cytogenetic maps depict the location and order of markers along chromosomes. Cytogenetic maps are important in genome research as they relate the genetic data and molecular sequences to the morphological features of chromosomes. In this paper, we discuss various methods used in cytogenetic mapping in maize, with special reference to fluorescence in situ hybridization (FISH) of single-copy sequences on meiotic pachytene chromosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 114 publications
0
5
0
1
Order By: Relevance
“…With the advance of genome research, cytogenetic maps will not only be valuable for integrating and organizing genetic, molecular, and cytological information, but they will also provide a unique insight into genome organization in the context of the chromosomes. In plants, two general approaches have been adopted for construction of a cytogenetic map (for reviews, see Harper and Cande, 2000;Wang and Chen, 2005). The first general strategy, widely used in wheat (Triticum aestivum), barley (Hordeum vulgare), tomato (Lycopersicon esculentum), maize, and others, is to locate genetically mapped DNA markers to chromosomal segments relative to cytologically mapped breakpoints using cytogenetic stocks (McClintock, 1944;Khush and Rick, 1968;Weber and Helentjaris, 1989;Beckett, 1991;Werner et al, 1992;Coe et al, 1993;Lin et al, 1997;Kunzel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With the advance of genome research, cytogenetic maps will not only be valuable for integrating and organizing genetic, molecular, and cytological information, but they will also provide a unique insight into genome organization in the context of the chromosomes. In plants, two general approaches have been adopted for construction of a cytogenetic map (for reviews, see Harper and Cande, 2000;Wang and Chen, 2005). The first general strategy, widely used in wheat (Triticum aestivum), barley (Hordeum vulgare), tomato (Lycopersicon esculentum), maize, and others, is to locate genetically mapped DNA markers to chromosomal segments relative to cytologically mapped breakpoints using cytogenetic stocks (McClintock, 1944;Khush and Rick, 1968;Weber and Helentjaris, 1989;Beckett, 1991;Werner et al, 1992;Coe et al, 1993;Lin et al, 1997;Kunzel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 2.4-kb DNA target can be detected on maize somatic chromosomes (Danilova and Birchler 2008). However, single-copy sequences 3.1-kb at the least can be detected on maize pachytene chromosomes (Wang et al 2006a), even though pachytene chromosomes of maize are about 12 times longer than their mitotic metaphase counterparts (Wang and Chen 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The present study has demonstrated the successful isolation of C 0 t-1 DNA from the B. napus genome. The C 0 t-1 DNA is routinely used as a blocking agent in in situ suppressive hybridization (Kahlem et al 2004;Dugan et al 2005;Wang and Chen 2005), so the isolated C 0 t-1 DNA of B. napus will be available for suppression hybridization of large B. napus genomic clones or genomic DNA in addition to chromosome banding.…”
Section: Discussionmentioning
confidence: 99%